Gone with the woof - Berenson, Laurien (Berenson, Laurien. Melanie Travis mystery., 2013)
Despite a toddler and a house full of Standard Poodles, Melanie Travis can<U+2019>t pass up an opportunity to help legendary dog breeder Edward March pen his life story. But her enthusiasm flags when the breeder<U+2019>s angry son, Andrew, demands she stop working on the book. The question of why becomes imperative once Andrew is killed by a seemingly intentional hit-and-run and the police are sniffing around for suspects. To get herself out of the dog house, Melanie sniffs out every possible clue, only to run into dead ends as fast as she<U+2019>s running out of time. And the longer the killer stays unleashed, the sooner she may hit her deadline<U+2026>